Evaluation of the satisfaction of users of a university library: analysis and proposals with a focus on the application of quality tools - Rodrigues, Stefane Dias (2020)
This study aims to evaluate the level of satisfaction of users of the library of a Higher Education Institution (HEI), using the SERVQUAL scale, which is a quality tool that compares users' expectations with their perception of a service and produce a discrepancy called Gap's. With this, this work collected the opinions of 261 respondents, which were tabulated to determine the individual Gaps by item studied and average Gaps by dimension also of the services of the university library of Abaetetuba. The results show that the dimensions of promptness and empathy assimilated an average of -2.312 and -2.034, the largest Gap’s among the dimensions studied. The perception of the promptness dimension, had the item with the highest perception, this refers to the acquisition of more copies for loan and consultation by users. The empathy dimension highlights the importance of free access by users to the collection and the appropriate collection with a variety of books on the same theme. After this evaluation, improvement proposals were elaborated using the quality tools, the PDCA cycle and the PSL-simplified method. The first proposed an improvement plan and also presented the need to carry out a rearrangement of the library layout. Thus, the simplified PSL was applied to discover the activity relationships and propose a new rearrangement of the layout. The SERVQUAL tool was able to assess that users are dissatisfied with the service provided, so it is suggested to apply the proposed PDCA cycle and adhere to the new layout.